Chinese Ecological Attitudes in the Modern Era and Foundations of Taoist Philosophy: : A Case Study of the “Biodiversity Conservation in China” Whitepaper - ซือฉี, เหยา (Journal of Letters, 2023)
This paper analyzed (1) the language representations of attitude resources in the “Biodiversity Conservation in China” whitepaper based on Martin and White’s appraisal theory, and (2) hidden modern Chinese eco-attitudes as reflected in the whitepaper. The findings were that the whitepaper used all three attitude subcategories: (1) judgment, (2) appreciation, and (3) affect, in decreasing order of significance. Judgment and appreciation were highly proportional and positive, while distribution of affect was minimal. Chinese eco-attitudes in the new era, as reflected in the white paper, may be considered from three perspectives: overall outlook, equality and future perspective. Ecological awareness of respecting and protecting nature may be awakened, influenced by the concepts of “heaven and man are united as one” and “Tao operates naturally” as fundamental philosophies in traditional Chinese culture. Promoting harmonious coexistence between humans and nature would boost natural resource protection and sustainable development.